Black ceramic spheres as marker grains for microfossil analyses, with improved chemical, physical, and optical properties. (7th October 2017) - Kitaba, Ikuko; Nakagawa, Takeshi
Abstract: Marker grain method is commonly used by palynologists to quantify absolute pollen concentration in sediments. DuPont NEM plastic microbeads and Lycopodium spore tablets are two of the most commonly used marker grains. The DuPont NEM series has an obvious advantage over Lycopodium tablets because Lycopodium is not guaranteed 'exotic' in many ecosystems (especially in the past). Moreover, NEM also has high visibility, easily identifiable spherical shape, and availability in different size ranges. However, the production of NEM has been discontinuous since more than a decade, and palynologists of the world are using the precious remainders of their own stock in very small (=suboptimal) quantities. Here we propose a solution. Microspheres of black ceramic can be used as marker grains for a wide range of microfossil analyses (in this paper, however, we mainly discuss the use of the material for pollen analysis because of the expertise of the authors). The ceramic spheres are tolerant to all chemicals commonly used during pollen extraction processes and is extremely resistant to physical stresses. The particles are matt black, spherical, available in a wide range of size clusters, have a density very close to that of fossil pollen grains (1.424 g/cm 3 vs. 1.494 g/cm 3 in average), and don't change color and density over a long storage in acidic liquids. The behavior of ceramic spheres was closer to the pollen grains than the Lycopodium spores regardless of the pollen concentration and composition in sediments. In combination, these properties make the black ceramic spheres an even better solution for palynologists than DuPont NEM microbeads or Lycopodium spore tablets. The absolute pollen concentrations estimated from ceramic spheres and those estimated from volume method were indistinguishable within errors. On the other hand, when the samples were relatively poor in fossil pollen grains, the concentrations calculated by Lycopodium method tended to be significantly overestimated. The ceramic microbeads are available either as a dry powder in different size ranges, or as a mixture of two size ranges blended in a defined ratio and dispersed in a buoyancy-neutral liquid, ready to be added to sediment samples. Mixing two different size ranges in a known ratio serves to detect any laboratory failures that differentially favor recovery of larger or smaller pollen types.